Neurodegenerative Diseases – Is Metabolic Deficiency the Root Cause? - Muddapu, Vignayanandam Ravindernath; Dharshini, S. Akila Parvathy; Chakravarthy, V. Srinivasa; Gromiha, M. Michael (Frontiers in Neuroscience, 2020)
Neurodegenerative diseases, including Alzheimer's (AD), Parkinson's (PD), Huntington (HD), and Amyotrophic Lateral Sclerosis (ALS), are the prominent class of neurological diseases currently without a total cure. They are characterized by an inexorable loss of a specific type of neurons. The selective vulnerability of a specific neuronal cluster (typically a subcortical cluster) in the early stages, followed by the spread of the disease to the higher cortical areas, is a typical pattern of disease progression. Neurodegenerative diseases share a range of molecular and cellular features, including protein aggregation, mitochondrial dysfunction, glutamate toxicity, calcium load, proteolytic stress, oxidative stress, neuroinflammation, and aging, resulting in neuronal death. Efforts to treat these diseases are often limited by the fact that they tend to address any one of the above pathological changes while ignoring others. Lack of clarity regarding a possible root cause that underlies all the above pathologies poses an important challenge. To search for an integrative theory of neurodegenerative pathology, we hypothesize that metabolic deficiency in certain vulnerable neuronal clusters is the common underlying thread that links the many dimensions of the disease. The aim of the current review is to present an outline of such an integrative theory. We present a new perspective of neurodegenerative diseases as metabolic disorders at molecular, cellular, and systems levels. This helps to understand the common underlying mechanism of the many facets of the disease and may lead to more promising disease-modifying therapeutic interventions. Here, we briefly discuss the selective metabolic vulnerability of specific neuronal clusters and also the involvement of glia and vascular dysfunctions. Any failure in satisfaction of the metabolic demand by the neurons triggers a chain of events that precipitate various manifestations of neurodegenerative pathology.